Development of food-origin biochars for the adsorption of selected volatile organic compounds (VOCs) for environmental matrices. (December 2021) - Kaikiti, Kyriaki; Stylianou, Marinos; Agapiou, Agapios
Graphical abstracts: Highlights: Pomegranate-, prickly pear-peels, carob and locust bean gum biochars were produced. Cresol, dimethyl trisulfide, hexane, and carcinogenic benzene were adsorbed. Pomegranate peels biochar at 550 ℃ proved as optimum towards the examined volatiles. It achieved ∼ 99% removal of 500 ppbv benzene, cresol, and dimethyl trisulfide. Food waste-based biochars enable the removal of malodorous livestock volatiles. Abstract: Four novel fruit-derived biochars were developed: pomegranate peels (PB), prickly pear peels (PPB), carob (CB), and locust bean gum (LBGB). The feedstocks were pyrolyzed at 350 and 550 ℃ (under N2 ), respectively, and characterized using Scanning Electron Microscopy (SEM), Elemental Analysis (EA), Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS), Brunauer–Emmett–Teller (B.E.T) analysis, and Thermogravimetric analysis (TGA). A systematic and comprehensive comparison for the adsorption of selected volatile organic compounds (VOCs) by biochar was established. Cresol, dimethyl trisulfide (DMTS), hexane, and benzene were examined as a function of contact time (30–480 min), mass (0.1–1 g), concentration levels (50–1000 ppbv ), efficiency, and reusability, using the headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC–MS) method. PB 550 ℃ revealed a specific surface area of 8.3 m 2 g −1, the fastest complete removal, an ideal mass of 1 g, 3-times reuse, and ∼ 99% removal of 500 ppbv benzene, cresol, DMTS, and 100 ppbv hexane.